2012
DOI: 10.5455/vetworld.2012.155-159
|View full text |Cite
|
Sign up to set email alerts
|

Study on the antimicrobial activity of Ethanol Extract of Propolisagainst enterotoxigenic Methicillin-Resistant Staphylococcus aureus in lab prepared Ice-cream

Abstract: The objective of this study was to investigate the antimicrobial activity of ethanol extract of propolis against enterotoxigenic strain of MRSA which inoculated into lab prepared ice cream. EEP was added to ice cream in 3 concentrations (150, 300 and 600 mg/L). The prepared ice cream was divided into 2 groups, one stored at freezer temp. at (-5°C), while the other was kept in deep freezer temp. at (-20°C). MRSA could not be counted from the th nd st 4 , 2 and 1 week of storage at freezer temp, while at deep fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…3P groups which contains 300 ppm propolis had a sim- and L. monocytogenes could not be counted at the end of 2 days of storage. Many in vitro studies showed that propolis extract has antibacterial effect on many spoilage and pathogenic foodborne Grampositive and Gram-negative bacteria (Boyanova, Kolarov, Gergova, & Mitova, 2006;El-Bassiony et al, 2012;Kim & Chung, 2011;Yang, Chang, Chen, & Chou, 2006). Additionally, Thamnopoulos et al (2018) reported that the ethanolic extract of propolis into glycerol showed the inhibition effects on L. monocytogenes in milk at the end of 30 days of storage.Propolis has many compounds that have possessed antimicrobial activity such as terpenoids, flavonoids, and some non-volatile compounds (Bankova et al, 2016;Thamnopoulos et al, 2018).…”
Section: Re Sults and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3P groups which contains 300 ppm propolis had a sim- and L. monocytogenes could not be counted at the end of 2 days of storage. Many in vitro studies showed that propolis extract has antibacterial effect on many spoilage and pathogenic foodborne Grampositive and Gram-negative bacteria (Boyanova, Kolarov, Gergova, & Mitova, 2006;El-Bassiony et al, 2012;Kim & Chung, 2011;Yang, Chang, Chen, & Chou, 2006). Additionally, Thamnopoulos et al (2018) reported that the ethanolic extract of propolis into glycerol showed the inhibition effects on L. monocytogenes in milk at the end of 30 days of storage.Propolis has many compounds that have possessed antimicrobial activity such as terpenoids, flavonoids, and some non-volatile compounds (Bankova et al, 2016;Thamnopoulos et al, 2018).…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…The determination of the chemical composition of the ice cream samples revealed that the use of propolis and combination of propolis and nisin in ice cream formulation had no significant effect on the fat, protein, ash, and total solids content (Table 4). The ice cream samples contained averagely 33% solid content, 4.6% fat, 3.13% protein, and 1.05% ash content.The ingredients added to food formulations at very low doses (ppm basis) are not expected to have a significant effect on food production technology and its composition.In the related literature, it is known that the similar ingredients which have antimicrobial and antioxidant properties have a significant effect on mostly sensorial properties of ice cream besides the effects on some microbiological and chemical reactions (Dean & Zottola, 1996;El-Bassiony et al, 2012).…”
Section: Re Sults and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…monocytogenes (Thamnopoulos et al, 2018), inhibit S. aureus (El-Bassiony et al, 2012), and increase the shelf life of yogurt (Ö zer, 2020). In this case, propolis can be used as an enrichment in food products, both as a natural additive, improving food quality, and as a natural preservative (Pobiega et al, 2018;Seibert et al, 2019).…”
Section: Fig 3 (Center)mentioning
confidence: 99%
“…However, data on the potential antimicrobial properties of propolis in dairy foods are scant: Costa et al. (2014) evaluated the antimicrobial effects of propolis-coated, active-packaging films (made with starch, glycerol, and cellulose nanocrystals) against coagulase-positive staphylococci in cheese curds and El-Bassiony et al. (2012) studied the antimicrobial activity of an ethanolic extract of propolis toward enterotoxigenic methicillin-resistant Staphylococcus aureus in laboratory-prepared ice-cream.…”
Section: Introductionmentioning
confidence: 99%